Часові параметри водонафтогазоносних осадових товщ за результатами створення і застосування реперного геохронографа. Стаття I - Хтема, А.В.; Хтема, В.М. (Геоінформатика, 2016)
Вивчення генези аномалій типу “вуглеводневий поклад” з використанням фізико-геологічної інтерпретації каротажних діаграм, структурно-числового моделювання та геоінформаційного робота зумовило необхідність формалізації, математизації і автоматизації процесу отримання стратиграфічних даних із застосуванням розрахункового модуля, що виконує функцію геохронографа. Основою геохронографа слугувала космофізична модель процесу еволюційного розвитку об’єктів Сонячної системи, яка створена з використанням досягнень теоретичної фізики і результатів астрономічних спостережень. Изучение генезиса аномалий типа “углеводородная залежь” с использованием физико-геологической интерпретации каротажных диаграмм, структурно-числового моделирования и геоинформационного робота обусловило необходимость формализации, математизации и автоматизации процесса получения стратиграфических данных с применением расчетного модуля, выполняющего функцию геохронографа. Основой геохронографа служила космофизическая модель процесса эволюционного развития объектов Солнечной системы, которая создана с использованием достижений теоретической физики и результатов астрономических наблюдений. The purpose of the paper is to give a detailed study of a deposit-type anomaly and hydrodynamic trap of the recycling type using a geo-information robot; to formalize, mathematize and automatize the stratigraphic data generation process. Design/methodology/approach. The method used is physical and geological well log interpretation, structural and numerical modeling, and creation of geoinformation digital technology based on it. This technology is based on exponential model of the Earth formation process applying time arrow.
Findings. Based on the theoretical physics and astronomical observation data, we created a cosmophysical model of the evolutionary growth process of objects in the planetary system. By applying this cosmophysical model, a datum geochronograph was designed.
Practical value/implications. Evidence on unobservable and non-measurable time characteristics of the Earth's interior unknown before was obtained in an automated way. This information can extend the theoretical and practical possibilities of stratigraphy by quantitative measurement of time. It is expected that the obtained geoinformation will help to raise the level of general geological understanding.